2012
DOI: 10.1186/1755-7682-5-12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malaria morbidity on gross domestic product in Uganda

Abstract: BackgroundThe burden of malaria is a key challenge to both human and economic development in malaria endemic countries. The impact of malaria can be categorized from three dimensions, namely: health, social and economic. The objective of this study was to estimate the impact of malaria morbidity on gross domestic product (GDP) of Uganda.MethodsThe impact of malaria morbidity on GDP of Uganda was estimated using double-log econometric model. The 1997-2003 time series macro-data used in the analysis were for 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 12 publications
1
39
0
2
Order By: Relevance
“…With 1.18 (Burkina Faso [18]), 3.5 (Nigeria [19]), and 0.98 (Uganda [20]) malaria episodes per year per child and a private household cost savings per episode of USD $2.82 (Burkina Faso), USD $1.86 (Nigeria), and USD $3.04 (Uganda), the projected total mean household cost savings at district level per year were USD $29 965 for Mangodara (Burkina Faso), USD $254 268 for Ona-Ara (Nigeria), and USD $303 467 for Sheema and Kayunga (Uganda). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With 1.18 (Burkina Faso [18]), 3.5 (Nigeria [19]), and 0.98 (Uganda [20]) malaria episodes per year per child and a private household cost savings per episode of USD $2.82 (Burkina Faso), USD $1.86 (Nigeria), and USD $3.04 (Uganda), the projected total mean household cost savings at district level per year were USD $29 965 for Mangodara (Burkina Faso), USD $254 268 for Ona-Ara (Nigeria), and USD $303 467 for Sheema and Kayunga (Uganda). …”
Section: Resultsmentioning
confidence: 99%
“…of malaria episodes per year, per child <5 y old a 1.183.500.98No. of children <5 y old b,c 900539 058101 862Mean household costs (USD) per episode (SD) d before intervention4.36 (10.3)3.90 (8.8)4.46 (8.7)Mean household costs (USD) per episode (SD) d during intervention1.54 (3.6)2.04 (6.6)1.42 (3.6)Savings per child (USD) per episode (SE) e 2.82 (0.6)1.86 (0.4)3.04 (0.5)Total mean savings (USD) per child and per year (SE) e 3.33 (0.7)6.51 (1.5)2.98 (0.5)Before intervention: total mean costs (USD) per year for malaria for the whole district46 329533 142445 218During intervention: total mean costs (USD) per year for malaria for the whole district16 364278 874141 751Total mean savings (USD) per year for malaria for the whole district29 965254 268303 467Abbreviations: SD, standard deviation; SE, standard error; USD, US dollars. a References [18–20] b References [21–23]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate study conducted in Uganda to determine the economic loss due to malaria showed that the economic burden of malaria reduced the Gross Domestic Product of Ugandans [5].…”
Section: Introductionmentioning
confidence: 99%
“…Okorosobo et al [12] used a combination of methods to estimate the economic burden of malaria in five AFR countries. Orem et al [13] used production function approach to estimate the impact of malaria morbidity on GDP in Uganda. Kirigia et al [14] used COI approach to estimate the indirect cost of maternal deaths in AFR.…”
Section: Introductionmentioning
confidence: 99%